The Legal Certainty and Protection of Foreign Investment Againsts Investment Practices in Indonesia - Ayu Taduri, Januari Nasya (Lex Scientia Law Review, 2021)
Foreign investment or well known as "Foreign Capital Investment" is one of the state's efforts to accelerate the pace of the Indonesian economy. So, it is not surprising that the Indonesian Government continues to carry out juridical reforms related to foreign investment. This renewal cannot be separated from the objective of providing certainty and guaranteeing legal protection for foreign investors, so that they can continue to carry out investment in the territory of the Republic of Indonesia. But the question that arises by the author, are the Indonesian laws and regulations sufficient to provide legal certainty in various aspects of investment, from licensing to dispute resolution? In response to this, this paper aims to further examine the legal certainty and protection of foreign investors in carrying out Foreign Direct Investment. The legal research method used is normative legal research through a statutory approach. In addition, this paper uses secondary legal data sources.